Fabrication and properties of highly transparent Er:YAG ceramics - Qin, Xianpeng (2013)
Highly transparent Er:YAG ceramics with different Er doping concentrations were fabricated by a reactive sintering method under vacuum. The optical properties and the microstructures of the Er:YAG ceramics were investigated. For 3 mm thickness samples, the in-line transmittances of the as-fabricated Er:YAG ceramics at the wavelength of 1100 nm and 400 nm were about 84% and 82%, respectively. The micrograph of the Er:YAG transparent ceramics exhibited a pore-free structure and the average grain size was about 10 μm. The grain boundary of the ceramics was clean and no secondary phase was detected. The absorption and emission spectra, the fluorescence decay traces of the Er:YAG ceramics were measured and discussed. The ceramics obtained may have potential use for eye-safe solid-state lasers partly replacing Er:YAG single crystals.